54 Investigating normal day to day variations in postural control in a healthy young population (age 18–40) using wii balance boards. (12th October 2015) - Johnston, W; Purcell, C; Duffy, C; Casey, T; Greene, BR; Singleton, D; McGrath, D; Caulfield, B
Abstract : Background: Objective measurements of postural control are frequently used to examine the causes of, features associated with, and therapeutic interventions for ankle instability. However, researchers have typically used single-session measures to represent postural control at one point in time. Recent studies in a healthy elderly population demonstrated significant variations in day-to-day postural control and suggest that single-session measurement may not truly reflect postural control. We need to investigate patterns of day-to-day variation in postural control in a younger population, the typical age profile included in ankle instability studies. Objective: Investigate the variations between continuous day-to-day clinical measurements of postural control within subjects, and the associations between once-off and continuous daily measurements, in a healthy young population. It was hypothesised that variations exist and a once-off clinical measure may not be representative of an individual's true postural control. Design: Observational longitudinal cohort study. Setting: University motion capture laboratory. Participants: 24 healthy young adults (9 female, 15 male) aged 18–40 years. Independent variables: Age, time of day (08:00–10:00), duration (40 s) and testing condition (eyes-open versus eyes-closed). Main outcome measurements: Lifestyle questionnaire and 40 s eyes-open/eyes-closed static Wii Balance Board balance tests, on 20 consecutive weekdays Results: Coefficient of variation demonstrated substantial inter-subject differences from 10–131% (eyes-open) and 10–112% (eyes-closed) across variables. Minimal detectable change percentage showed that 22/30 parameters demonstrated acceptable measurement error (<30%). Across mean COP distance, mean sway length, mean sway frequency and sway area, 16/24 (eyes-open) and 11/24 participants (eyes-closed) exhibited statistically significant differences ( p < 0.05) between the once-off and the daily measures. Conclusion: Variations in postural control exist in a healthy young population. Depending on testing conditions and specific variables, a once-off measure is not indicative of an individual's true functional state. Therefore, when investigating subtle changes in postural control, long-term monitoring proves to be a superior assessment tool.